TRANSFORMASI FINANCIAL TECHNOLOGY PADA PENGELOLAAN PRODUK HASIL EKONOMI KREATIF UNTUK MENINGKATKAN EKONOMI MASYARAKAT DI DESA WISATA PARDOMUAN MOTUNG - William Liang; Novendra Adisaputra Sinaga; Erikson Damanik (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
The urgency of this research is to build a technology-based financial system that is used by the creative economy community in Pardomuan Motung Village in managing their products. The system built is a form of transformation from a conventional financial management model to a technology-based one. The results of this research have had a big influence on the economic conditions of the business world in Pardomuan Motung because since the Covid-19 pandemic until post-pandemic there have been major changes in financial and business governance in Indonesia from traditional to modern. continue to innovate. So, if the governance and financial system of the creative economy community in Pardomuan Motung Village does not transform, then the businesses they are involved in will find it difficult to develop and compete. The aim of this research is to create a technology-based financial system for managing creative economic products to improve the community economy in the Pardomuan Motung Tourism Village. The system to be built includes financial technology that allows users to carry out financial processing, recording systems and various financial transactions online. The result of this research is a design for an accounting recording system that will be used as a medium for recording all accounting transactions and will produce complete and accurate financial information.